Predictors of persistent active disease and the longitudinal development of organ damage, patient-reported outcomes and autoantibodies in long-term juvenile dermatomyositis - Helga Sanner; Ivar Sjaastad; Henriette Schermacher Marstein; Kristin Schjander Berntsen; Kristine Risum; Mathis Korseberg Stokke; Simon Girmai Berger (RMD Open)
Objective To quantify longitudinal development of disease activity, organ damage, patient-reported outcomes, and myositis autoantibody profiles in patients with juvenile dermatomyositis (JDM) after long-term follow-up, and to identify predictors for persistent active disease.Methods Forty patients (65% female) diagnosed with JDM were clinically examined at two different time points (visits 1 and 2). We assessed clinically inactive/active disease by the updated PRINTO criteria and the Juvenile DermatoMyositis Activity Index (JDMAI). Organ damage was evaluated by Myositis Damage Index (MDI) and physical function by Childhood Health Assessment Questionnaire (CHAQ/HAQ). Myositis autoantibodies were measured by myositis line immunoassay.Results Median disease duration from symptom onset was 15.1 (2.0–34.6) at visit 1 and 21.7 (7.6–42.7) years at visit 2. At visit 2, active disease (PRINTO) was found in 53%, impaired physical function (CHAQ/HAQ>0) in 40%, organ damage (MDItotal≥1) in 95% and myositis specific or associated antibodies in 33% of patients. Disease activity (JDMAI) was low in 24%, moderate in 8% and high in 3% of patients. There were no significant differences in organ damage and disease activity between visits. Higher disease activity and organ damage at visit 1 predicted persistent active disease at visit 2.Conclusions After a median of 21.7 years from symptom onset, the majority of JDM patients still had active disease. Higher organ damage and disease activity at the initial visit predicted persistent active disease at follow-up. These results underscore the chronic nature of JDM, emphasising the need for enhanced early and long-term management strategies to improve patient outcomes.